Empowering Pondok Pesantren Al Barokah Dalam Agribisnis Jamur Untuk Meningkatkan Pendapatan Dan Kesejahteraan Para Santri - Lidyana, Novita; Bahri, Moh. Saiful; Yatiningrum, Agung; Tyas, Yayuk Indah Wahyuning; Dhany, Umi Rahma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2022)
Empowering aims to increase people's income through agribusiness, mushroom cultivation and improve skills for the community, especially students at the Pondok Pesantran Al Barokah Mojolegi Wangkal Kraksaan Probolinggo which brings many benefits in the form of: (1) Mastery of free time with useful business. (2) Utilization of residual land for useful business activities, (3) Expansion of diversification in the field of farming, (4) Increased knowledge, skills, and insights in the field of cultivation, especially oyster mushroom agribusiness, (5) Improved management skills, especially in marketing field. This community service activity for oyster mushroom cultivation was carried out at the Pondok Pesantren Al Barokah Mojolegi, Wangkal, Probolinggo Regency. The results obtained are that the students have high enthusiasm to take part in counseling activities and foster oyster mushroom cultivation, as an effort to get a source of income outside of their parents' gifts. And also for the management of the Pondok Pesantran Al Barolah Mojolegi Wangkal, Probolinggo Regency, providing opportunities for resource persons to socialize community service programs to their students to start quite a lot of activities, so the students need support from both the cottage manager and intensive guidance from resource persons. for this activity to be successful.